Optimizing patient selection for stereotactic ablative radiotherapy in patients with locally advanced pancreatic cancer after initial chemotherapy - a single center prospective cohort - Doppenberg, D.; Lagerwaard, F. J.; van Dieren, S.; Meijerink, M. R.; van der Vliet, J. J.; Besselink, M. G.; van Tienhoven, G.; Versteijne, E.; Slotman, B. J.; Wilmink, J. W.; Kazemier, G.; Bruynzeel, A. M. E. (Frontiers in Oncology, 2023)
Background: The role of stereotactic ablative radiation therapy (SABR) as local treatment option after chemotherapy for locally advanced pancreatic cancer (LAPC) is evolving. However adequate patient selection criteria for SABR in patients with LAPC are lacking. Methods: A prospective institutional database collected data of patients with LAPC treated with chemotherapy, mainly FOLFIRINOX, followed by SABR, which was delivered using magnetic resonance guided radiotherapy, 40 Gy in 5 fractions within two weeks. Primary endpoint was overall survival (OS). Cox regression analyses were performed to identify predictors for OS. Results: Overall, 74 patients were included, median age 66 years, 45.9% had a KPS score of ≥90. Median OS was 19.6 months from diagnosis and 12.1 months from start of SABR. Local control was 90% at one year. Multivariable Cox regression analyses identified KPS ≥90, age <70, and absence of pain prior to SABR as independent favorable predictors for OS. The rate of grade ≥3 fatigue and late gastro-intestinal toxicity was 2.7%. Conclusions: SABR is a well-tolerated treatment in patients with unresectable LAPC following chemotherapy, with better outcomes when applied in patients with higher performance score, age <70 years and absence of pain. Future randomized trials will have to confirm these findings.